PATH-29. CLINICAL SIGNIFICANCE OF TEMOZOLOMIDE-INDUCED SOMATIC HYPERMUTATION IN INITIALLY LOW-GRADE IDH-MUTANT DIFFUSE GLIOMAS. (5th November 2018) - Yu, Yao; Hilz, Stephanie; Grimmer, Matthew; Solomon, David; Choi, Serah; Wahl, Michael; Mazor, Tali; Hong, Chibo; Shai, Anny; J Phillips, Joanna; Villanueva-Meyer, Javier; McDermott, Michael; et al.
Abstract: INTRODUCTION: Diffuse low-grade gliomas (DLGG) treated with temozolomide (TMZ) can develop somatic hypermutation. We present data on the incidence and prognostic importance of somatic hypermutation in IDH-mutant DLGGs. METHODS: We analyzed 120 patients treated on a phase II clinical trial of TMZ for sub-totally resected DLGGs to estimate the risk of recurrence and transformation after TMZ. To understand the prognostic significance of somatic hypermutation, we determined hypermutation status by exome or targeted sequencing on tumors from 81 patients with recurrent IDH-mutant DLGGs. 63/81 patients received TMZ before recurrence, including 28 patients treated on-trial. RESULTS: With median follow-up of 8.7 years, 89 patients from the phase II trial progressed, 60 underwent 1 re-operation, and 36 had histologically confirmed transformation. The 8-year freedom from transformation was 48.2% and 59.9% for IDH-mutant astrocytomas and oligodendrogliomas, respectively; risk of transformation increased with pre-TMZ tumor volume (HR 2.5 per 100cc, p<0.001). In the recurrent glioma cohort, 65/81 patients transformed to grade III or IV; hypermutation was identified at transformation in 30/53 (57%) treated with TMZ. Hypermutation occurred in 31 patients all had received TMZ and 30/31 had developed transformed tumors. Analyzing by specimen, hypermutation was associated with transformation (bootstrapped logistic regression p < 0.001). After transformation to grade III disease (n=47), hypermutation was associated with diminished survival (HR 5.6, p=0.007), controlling for molecular subtype and age at diagnosis. Patients with transformation to glioblastoma (n=18) had poor prognosis regardless of hypermutation (p=0.53). Four cases of spinal dissemination were identified, all of whom had hypermutated gliomas. CONCLUSIONS: Somatic hypermutation is common in transformed, initially low grade IDH-mutant diffuse gliomas treated with TMZ. After anaplastic transformation, somatic hypermutation is associated with reduced survival, independent of molecular subtype. These data have implications for the management of newly diagnosed and recurrent DLGG, and indicate a potential role for immunotherapy.